Remodeling of Tumor Immune Microenvironment by Oncolytic Viruses - Zhang, Bin; Wang, Xilei; Cheng, Ping (Frontiers in Oncology, 2021)
Oncolytic viruses (OVs) have potential to become part of tumor immunotherapy as an antitumor active pharmaceutical agent. OVs can directly modify tumor cells and can have beneficial impact on tumor treatment. Genetically engineered oncolytic virus can be designed to evade the host antiviral immunity and target the tumor by remodeling the tumor immune microenvironment. This article mainly explores the effectiveness of genetically engineered OVs in remodeling the tumor immune microenvironment, regulation of the host immune system, immune cell activation and recruitment, escape from immune suppression, and ultimately enhancement of immune cell function. Furthermore, the article also focuses on how OVs can be harnessed for exogenous cytokines expression and can be used as expression vectors for immunomodulatory antibodies, thereby enhancing our ability to treat tumors and optimizing immunotherapy.